STEADY STATE CONDITION PREDICTION OF ECONOMIC GROWTH IN EAST JAVA REGION - Sutikno, Sutikno (Jurnal Ekonomi Pembangunan, 2019)
The quality of development of a country or region is not only seen from the high level of economic growth, but also the higher level of economic growth produced by people in a country or region. One of the economic development debates in East Java in the last few decades is the imbalance of development between regions. This article focuses its analysis on the value of "stable conditions" districts / cities in East Java in reducing income disparity between regions. The analysis in this study is a convergence analysis conducted in East Java Province using a conditional convergence test with observations of all districts and cities in East Java. Variable interest is income per capita. Variable gross fixed investment, net exports, labor force, capital expenditure, human development index. The success variable is the average economic growth in 2010-2018. Whereas the theory underlying all these variables is the Solow-Swan classical economic growth model. The convergence speed results explain the convergence speed in East Java Province by 4.8 percent. Regarding income per capita in developing countries which must grow at least 4.8 percent per year for the Java economy to reach a stable point. The amount of time needed to cover half of the initial period (half-life of convergence) is 6.2 years